The Test-Retest Reliability of Heart Rate Variability and Its Association With Personality Functioning - Eikeseth, Fillip Ferreira; Sætren, Sjur Skjørshammer; Benjamin, Beatrice R.; Ulltveit-Moe Eikenæs, Ingeborg; Sütterlin, Stefan; Hummelen, Benjamin (Frontiers in Psychiatry, 2020)
Background: Heart rate variability (HRV) is a widely used non-invasive index of emotion regulation ability. The main aim of our study was to investigate the relationship between HRV and level of personality functioning in a clinical sample, most of whom had a personality disorder. Our secondary aim was to examine the test-retest reliability of HRV in our sample as there is a lack of knowledge regarding the test-retest reliability in psychiatric populations. We hypothesized that trait HRV would be negatively associated with impairment of personality functioning. Method: Thirty-two adults (23 females, mean age = 27) with threshold or subthreshold personality disorders were recruited from two psychiatric outpatient clinics in Norway. Impairment of personality functioning was assessed by the first module of the Structured Clinical Interview for the DSM-5 Alternative Model for Personality Disorders (SCID-5-AMPD-I); Level of Personality Functioning Scale (LPFS). HRV was assessed during resting conditions with spontaneous breathing over three separate days. Trait HRV was calculated by averaging all three HRV assessments. The test-retest reliability of HRV was assessed using intraclass correlations. Results: Contrary to expected, a positive association between trait HRV and the LPFS Self-direction domain emerged. This was driven by positive associations between the LPFS and HRV at time point 2. Overall, the test-retest reliability of HRV was comparable to previous studies on healthy subjects. However, the reliability coefficients for the first two time points were considerably lower relative to the second and third time points. Conclusions: We propose that impairment of personality functioning may have increased the proportion of variance in HRV attributed to state relative to trait. This could explain the lower test-retest reliability for the first two time points. The increased test-retest reliability for the last two time points could reflect a habituation to the testing situation and hence, less pronounced influences of state in the second and third time points.